Adherence, Quality of Life, and Determinant Factors among Patients with Chronic Kidney Disease Undergoing Hemodialysis: A Cross-Sectional Analysis - Wenny Trisnaningtyas; Novita Kusuma Wulandari; Sherly Metasari; Nina Indriyawati; Ana Permatasari; Sawab; Rodhi Hartono; Wahyu Sukma Samudera (Journal Of Nursing Practice, 2026)
Background: Hemodialysis sustains life for chronic kidney disease patients but imposes heavy physical, psychological, and social burdens. Poor adherence worsens complications and reduces quality of life, emphasizing the need to explore how compliance and patient well-being interact to improve outcomes. Purpose: This study examined how quality of life and patient factors shape treatment adherence in chronic hemodialysis. Methods: A cross-sectional design was employed with 158 adult patients recruited from hospitals in Central Java. Data were collected using validated instruments: KDQOL-36 for quality of life and MMAS for adherence. Multivariable linear regression analysis was performed to examine associations between variables. Results: Moderate adherence was observed (47.66 ± 5.90), with the highest quality of life domain in the problem list (78.30 ± 9.67). Strong positive correlations were found between adherence and all QoL domains: SF-12 (r = 1.000, p < 0.001). Regression analysis showed that age, employment, education, income, dialysis duration, and CKD length negatively influenced adherence, while quality of life was a significant positive predictor (B = 0.021, p < 0.001), confirming that better adherence is strongly linked to improved quality of life across physical, psychological, and social domains, with patient-reported challenges being the most critical factor. Conclusion: Quality of life influences adherence by affecting burden, motivation, and self-management, while age and longer dialysis history weaken this link through fatigue and reduced resilience. Socioeconomic factors help only with psychosocial support, so nursing should reduce treatment burden.